Digital planning of educators and education at MA Raadhiyatan Mardhiyyah Putri Balikpapan - Khalifatuzzahrah A.J; Endin Mujahidin; Imas Kania Rahman; Nesia Andriana; Darling Hammond (At Turots: Jurnal Pendidikan Islam, 2025)
Planning is an effort to achieve goals optimally. In addition to achieving goals, planning is carried out so that everything that is done is more organized and more useful. Human resources (HR) are the most important part and are even very closely related to companies, organizations, or ministries because it is human resources who carry out the planning stages. Educators and education personnel are human resources in the realm of education. In addition to achieving goals, good planning is also carried out so that educational institutions can survive and grow in the midst of competition and progress of the times, especially in the rapid development of technology. The problem that often occurs in planning educational institutions, especially Islamic educational institutions of Islamic boarding schools, is the immaturity of the planning carried out. The purpose of this study is to find out how and who is responsible for the parts in the planning of educators and education at MA Raadhiyatan Mardhiyyah Putri Balikpapan. The method used in this study is a qualitative research method with a descriptive type. Data were collected through online unstructured interviews and analysis of official documents from the study site, as well as literature supported by relevant reference sources. Data analysis through narrative analysis and content analysis. The respondents in this study were the head of the Women's Cadre Education Department (DP3) and the principal of MA Raadhiyatan Mardhiyyah Putri Balikpapan. The planning at MA Raadhiyatan Mardhiyyah Putri Balikpapan is quite good because it has been carried out according to procedures, ranging from needs analysis to termination of employment. It seems to narrow the opportunities for people from outside the institution to work inside, but the reason is acceptable because it concerns educators who will become uswatun hasanah for students. Each educational institution has different goals, of course, the criteria for educators as a control must be in accordance with these goals.